Prediction of potential habitat of Isodon amethystoides in China under climate change based on optimized MaxEnt model - Ji, Qiya; Chen, Shimao; Cao, Yunan; Xiang, Xiaosu; Sun, Yunyun; Zhang, Yan; Xing, Wanbo; Wang, Yanyan; Yang, Qingshan (Frontiers in Plant Science, 2025)
Isodon amethystoides (Benth.) H. Hara, a plant species belonging to the genus Isodon in the Lamiaceae family, possesses multiple medicinal properties including heat-clearing and detoxifying effects, anti-inflammatory and antibacterial activities, as well as liver-protective functions. Due to the challenges in harvesting from wild sources, current production primarily relies on artificial cultivation. Compared with wild resources, artificial cultivation not only improves medicinal material quality through standardized planting practices, but also enhances the content of bioactive components. Furthermore, it enables scientific evaluation of environmental factors’ impact on medicinal quality. This study uses the Maxent model to predict the current and future potential distribution areas and suitable habitats for Isodon amethystoides. Based on 194 species occurrence records and 90 environmental variables, we identified key environmental factors influencing its distribution through correlation analysis and variable contribution assessment, followed by model parameter optimization. The optimized model achieved an AUC value of 0.902, demonstrating excellent predictive performance. The results demonstrated that under current climatic conditions, the total suitable habitat area for Isodon amethystoides was estimated at 2.08×106 km², accounting for 21.66% of China’s terrestrial land area. The key environmental factors affecting the distribution of potential suitable habitats for Isodon amethystoides are precipitation in September, monthly precipitation, and standard deviation of seasonal temperature variation. Under future climate change scenarios (SSP1-2.6 and SSP5-8.5), the total suitable habitat area of Isodon amethystoides shows an overall increasing trend. By the 2050s, the suitable area is projected to reach its maximum extent approximately 2.48×106 km², with primary expansion occurring toward the northwest. Notably, Yunnan Province exhibits significant habitat expansion, while the centroid of suitable habitat consistently remains located in Chongqing. This study provides scientific support for the conservation of wild Isodon amethystoides resources and the planning of cultivation areas, thereby contributing to sustainable development and ecological protection.